(untitled) (Bangladesh Journal of Botany, 2008)
An experiment was carried out during 2001-2002 on the effect of different concentrations of potassium naphthenate (KNap), applied as foliar spray on yield and yield attributing characters of cowpea (Vigna unguiculata (L.) Walp.) grown in early Rabi season. Results indicated that the four concentrations of KNap had significatly positive effects on almost all reproductive parameters. 1500 KNap gave higher values than three other concentrations. Â Â Key words: Cowpea, Vigna unguiculata, Potassium napthenate, Yield attributes, Yield doi:10.3329/bjb.v36i1.1546 Bangladesh J. Bot. 36(1): 29-32, 2007 (June)